373. Impact of Concurrent Renal Replacement Therapy on Treatment Outcomes of Candidemia in Adults. (26th November 2018) - Hill, Brandon; Wilson, Dustin; Drew, Richard
Abstract: Background: Treatment of candidemia is complex. Studies examining relationships between patient-related factors and treatment outcome are limited, often based on all-cause mortality. Our objectives were to compare concurrent prespecified factors between patients with and without treatment failure among adults with candidemia. Methods: This IRB-approved, single-center, case-cohort study included patients >18 years old admitted to Duke University Hospital between June 1, 2013 and June 1, 2017 with a blood culture positive for Candida spp. Treatment-, patient-, and disease-specific data were collected, and outcome (success/failure) determined 90 days after the index culture. An odds ratio (OR) and 95% confidence interval (95% CI) were determined for receipt of renal replacement therapy (RRT), fluconazole-containing regimen, ICU stay, and neutropenia between outcome groups. Results: Among the 112 encounters (from 110 unique patients) included, treatment success was observed in 104/112 (92.9%). Demographics were comparable between treatment success and treatment failure groups. Among patients receiving concomitant RRT, 11/12 encounters (91.7%) were successfully treated. No significant differences were observed with regards to treatment failure with a fluconazole-containing regimen (OR, 1.59; 95% CI, 0.3–8.27), ICU stay (OR, 1.43; 95% CI, 0.32–6.29), and neutropenia (OR incomputable due to 0 treatment failures). Conclusion: Treatment success occurred in 91.7% of adult patients receiving concomitant RRT while undergoing treatment for candidemia. Treatment with a fluconazole-containing regimen, RRT, ICU stay, and neutropenia did not differ between the treatment outcome groups. Disclosures: All authors: No reported disclosures.